The Feminisation of War in the Contemporary Easter Rising Narratives of Mary Morrissy and Lia Mills - Morales-Ladrón, Marisol (ABEI Journal, 2016)
Traditionally, war and revolution, as male-oriented duties, kept women not only relegated to the domestic sphere but uninformed about whatwas regarded as more serious concerns. However, if men were involved in the war effort, the daily struggle belonged to women, even though they have remained outside mainstream historical accounts and their stories have been silenced or hidden from official accounts. With the intention of restating such imbalance, many Irish writers have engaged in the recovery of forgotten figures from the past, paving the way for the emergence of a renewed type of historical novel that offers alternative readings from a gender perspective. This would be the case of authors Julia O’Faolain, Emma Donoghue, Evelyn Conlon, Anne Enright or Henrietta McKervey, among a growing list. Within this panorama,two novels stand out, Mary Morrissy’s The Rising of Bella Casey (2013) and Lia Mills’s Fallen (2014). Both explore female subjectivity at times of war and delve into the struggle the protagonists have to face at a time of nationalist upheaval, while the male leaders of the uprising merely remain backstage, thus subverting mainstream accounts on the foundational myth of Ireland and demystifying revolutionary heroism. Considering these circumstances, the present discussion will attempt to demonstrate that these women played a more “revolutionary” role than the one attributed by history and will argue that these novels endeavor to bring women back to national history.Keywords: Mary Morrissy, Lia Mills, Easter Rising, First World War, history, revolution.